Cow weight and preweaning performance of calves - Singh, A.R.; Schalles, R.R.; Smith, W.H.; Kessler, F.B. (Kansas State University. Agricultural Experiment Station, 2011)
The influence of cow weight at parturition and during the lactation on preweaning performance of calves was evaluated. Hereford cattle at the Fort Hays Branch Experiment Station were used. Purebred sires had been used many generations in the herd that produced the calves. The calves were born January through April. Cows and calves grazed native pastures without creep feed. Heifers were bred to produce first calves when about three years old. All male calves were castrated by one month of age. Calves were weighed and identified within 24 hours after birth and were again weighed at weaning. They were weaned between September 15 and November 1, at an average age of 263 days. Cows were weight immediately following parturition and when the calves wore weaned.
Keywords: Beef; Cow weight; Performance; Average daily gain